The Relationship Between Future Time Perspective and Self-Esteem: A Cross-Cultural Study of Chinese and American College Students - Lyu, Houchao; Du, Gang; Rios, Kimberly (Frontiers in Psychology, 2019)
The present study explored cross-cultural differences in future time perspective and self-esteem and investigated whether the relationship between future time perspective and self-esteem differs between China and America. The Future Time Perspective Scale and Rosenberg Self-Esteem Scale were administered to 460 Chinese and 340 American undergraduates. Results showed that American undergraduates scored higher on the future-negative, future-positive, future-confusion, future-perseverant, and future-perspicuity subscales than did Chinese undergraduates; American undergraduates also had higher self-esteem than did Chinese undergraduates. The dimensions of future time perspective (future-negative, future-positive, future-confusion, and future-perseverant) significantly predicted self-esteem in both the Chinese and American samples. These results broaden our understanding of cross-cultural differences in future time perspective and self-esteem. Implications and future directions are discussed.